Analysis of the influence of thermal and thermocyclic technology on the properties of maraging steel - Ashurov Zhasur; Juraeva Malokhat; Pardaev Azimjon (E3S Web of Conferences, 2024)
The article presents experimental data obtained by studying the influence of changes in the geometry of parts made of maraging steels, depending on the modes of thermal and thermal cycling treatment with heating in the temperature range of α-γ transformation. The experiments were carried out on samples cut from hot-rolled sheets, pre-hardened at a temperature of 1000°C for 1 hour. Using the accelerated testing method, the relative change in resistance to stress corrosion damage was determined depending on the phase composition and aging temperature (strength) of maraging steel.